War, education and identity : discord at the Transvaal University College (1914-1919) (Historia, 2021)
Before the outbreak of World War I (1914-1918), broad South Africanism appeared to have had a tentative but solid beginning at the Transvaal University College (TUC). This international conflict, however, re-ignited tensions among white South Africans, and students at the TUC were no exception. The proximity of these events to the establishment of the College seemed to push the ideal of broad South Africanism at the College beyond reach. This article considers the striking effect of World War I and the 1914 Rebellion on the consciousness of the TUC students as seen in student contributions to The T.U.C. Students' Magazine and other events at the College. It examines in particular changing and conflicting notions of white identity at the College at this time.  Voor die begin van die Eerste Wêreld Oorlog het dit geblyk asof breë Suid-Afrikanisme 'n tentatiewe maar stewige begin by die Transvaalse Universiteitskollege (TUK) gehad het. Maar hierdie internasionale konflik het weer spanning tussen blanke Suid-Afrikaners veroorsaak en in hierdie opsig was TUK studente geen uitsondering nie. Die feit dat hierdie gebeure so kort na die stigting van die Kollege plaasgevind het, het die verwerkliking van die ideaal van breë Suid-Afrikanisme by die Kollegebaie moeilik gemaak. Hierdie artikel oorweeg die blywende indruk wat die Eerste Wêreld Oorlog en die 1914 Rebellie op die bewussyn van die studente van die TUK gelaat het soos uitgebeeld in die studentebydrae tot Die T.U.K. Studenteblad en in ander gebeurtenisse by die Kollege. Dit kyk spesifiek na veranderende en teenstrydige idees van blanke identiteit by die Kollege in hierdie tydperk.
Keywords: University of Pretoria; Universiteitsgeskiedenis; Transvaal University College; Broad South Africanism